Estrategias semiolingüísticas para el desarrollo de la competencia comunicativa y sus subcompetencias: Semiolinguistic strategies for the development of communicative competence and its sub-competencies - Bracho, Isabel (Quórum Académico, 2025)
The aim of this study was to design semiolinguistic strategies to develop students’ communicative skills and subskills in Spanish as a second language class at Ridge Point High School in Missouri City, Texas in the United States. The foundational theory was based on authors like Lomas (1999), Garcia de Molero (2011, 2014), Villasmil, Fuenmayor y Garcia de Molero (2014) related to the following criteria: 1. Communicative skills and subskills notions, 2. Semiotic theory of didactic communication, 3. Semiolinguistics strategies. The research was qualitative, and its sample was composed of 45 students. This research revealed that students at Ridge Point High School developed their lexical and sociocultural skills further after the applied strategies. Therefore, it is recommended that teachers take into account situational, social, and cultural aspects to develop communicative skills.